2014
DOI: 10.1371/journal.pone.0111474
|View full text |Cite
|
Sign up to set email alerts
|

Using the WHO Essential Medicines List to Assess the Appropriateness of Insurance Coverage Decisions: A Case Study of the Croatian National Medicine Reimbursement List

Abstract: PurposeTo investigate the use of the WHO EML as a tool with which to evaluate the evidence base for the medicines on the national insurance coverage list of the Croatian Institute of Health Insurance (CIHI).MethodsMedicines from 9 ATC categories with highest expenditures from 2012 CIHI Basic List (n = 509) were compared with 2011 WHO EML for adults (n = 359). For medicines with specific indication listed only in CIHI Basic List we assessed whether there was evidence in Cochrane Database of Systematic Reviews q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Regarding healthcare, changes in supply, access and funding have been highlighted [ 60 ], and from the perspective of health financing, the most important is the compulsory health insurance for all citizens [ 59 ]. Although citizens benefit from compulsory insurance, the introduction of taxes for using public and private facilities has led to an increase in the costs supported by the population [ 61 ], and some patients risking falling into ‘the medical poverty trap’ [ 62 ]. Therefore, it is necessary to rationalize spending so as to ensure wider and better access to medicines [ 63 ], mainly for low-income countries.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding healthcare, changes in supply, access and funding have been highlighted [ 60 ], and from the perspective of health financing, the most important is the compulsory health insurance for all citizens [ 59 ]. Although citizens benefit from compulsory insurance, the introduction of taxes for using public and private facilities has led to an increase in the costs supported by the population [ 61 ], and some patients risking falling into ‘the medical poverty trap’ [ 62 ]. Therefore, it is necessary to rationalize spending so as to ensure wider and better access to medicines [ 63 ], mainly for low-income countries.…”
Section: Methodsmentioning
confidence: 99%
“…There are also encouragements to supply policy-making process with stylised facts. Jelicic Kadic et al ( 2014 )call for using high-quality evidence in Croatian health care policy to rationalize expenditures and to ensure wider and better access to medicines. Zhang et al ( 2015 ) consider China’s National Reimbursement Ratio as a helpful quantitative indication in assessing and predicting national health insurance system.…”
Section: Introductionmentioning
confidence: 99%
“…The alignment of the WHO EML with the national reimbursement list of medicines was studied in Croatia and the Federation of Bosnia and Hercegovina (Kadic et al, 2014 ; Mahmić-Kaknjo and Marušić 2015 ). The WHO Essential Medicines List was used as a tool to assess the appropriateness of Insurance Coverage Decisions in the Croatian National Medicine Reimbursement List in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…From the 2012 Croatian Institute of Health Insurance Basic list (CIHI list) 9 ATC categories with the highest expenditures were compared with the 2011 WHO EML. The result of the study showed that, of the 9 ATC categories compared, the lists shared 188 medicines (52.4% of the WHO EML and 36.9% of the CIHI list) (Kadic et al, 2014 ). A study conducted in 2015 in Bosnia and Hercegovina compared the Basic Medicines Lists of the Federation of Bosnia and Hercegovina (FBH Basic Lists (FBLs)) with the WHO Essential Medicines list and the evidence supporting the inclusion of additional medicines on the FBLs.…”
Section: Discussionmentioning
confidence: 99%